On the Hyers-Ulam Stability of Differential Equations of Second Order - Qusuay H. Alqifiary; Soon-Mo Jung (Abstract and Applied Analysis)
By using of the Gronwall inequality, we prove the Hyers-Ulam stability of differential equations of second order with initial conditions.